Critical discourse analysis on gender relations: women's images in Sasak song - Khirjan Nahdi; Usuludin Usuludin; Herman Wijaya; Muh. Taufiq (Jurnal Konseling dan Pendidikan, 2019)
Sasak song as one form of artistic discourse is used as an instrument of male domination of women in gender relations through various forms of imaging that do not benefit women. The image is understood through the process and mechanism of work of critical discourse analysis. This study aims to reveal the image of women in the Sasak song by discovering the tendency of social construction in gender relations between men and women based on the principles of Critical Discourse Analysis. Through the position of the Sasak song text, the importance of the text, and the consequences of the text in the social reality of gender relations between men and women, found six images of women in the Sasak song text, namely women as male subordination; women as inferior, resigned women, cheap women, dependent women, and women without choice. As a text, discursive reasoning, and social reality, the results of the study show the tendency to dominate women who give birth to forms of discrimination. The six images of women in Sasak song texts are contained in works of art for the purpose of disguising the tendencies behind artistic elements, so that they are accepted as truth and reasonableness in history inherited between generations.